Hahnia corticicola Bosenberg & Strand 1905 - Marusik, Yuri M.; Koponen, Seppo (Zenodo, 2000)
Hahnia corticicola (Bösenberg & Strand, 1905) * Material examined: 3 ♂ ♀, [19] 43º25'N 133°28'E, short stop on creek, 9.08.1998, YM; 89 ♂ ♀, [12] 43º55'N 134º23'E, Pravava Izvilinka Riv, 1-2.08.1998, YM.; 42 ♂ ♀, [13] 43º52'N 134º17'E, Pravaya Izvilinka Riv, 2.08.1998, YM.; 2 ♀♀, [18] 43º17'N 134º12'E, short stop on creek, 5.08.1998, YM; 1 ♀, [09] env. of Anisimovka Vill, Kangaus River 43º06'N 132º47'E, 28.07- 9.08.1998, YM; 39 ♂ ♀, [17] Lazovski Reserve, Korpad’ Camp, 43º16'N 134º08'E, 6-9.08.1998, YM; 10 ♀♀, Lazovski Reserve, America Kordon, 43º16.5'N 134º03'E, 14- 17.05.1999, YS; 1 ♀, Lazovsky Reserve, Proselochny Kordon, 43º00.5'N 134º08'E, 4 — 6.10.1999, YS; 19 ♂ ♀, Lazovsky Distr, Gersimov River, 43º24'N 133º53.7'E, 13.09.1998, YS; 1 ♂ 1 ♀, Lazo Town, Lazovka River valley, 43º23'N 133º54'E, 17.04.1999, YS. COMMENTS. The first record in the province, earlier reported from Magadan and Sakhalin areas [Marusik & Logunov, 1991]. In addition to Russia, known also from Korea, Japan and China [Song et al., 1999]. : Published as part of Marusik, Yuri M. & Koponen, Seppo, 2000, New data on spiders (Aranei) from the Maritime Province, Russian Far East, pp. 55-68 in Arthropoda Selecta 9 (1) on page 60, DOI: 10.5281/zenodo.822713 : {"references": ["Marusik Yu. M., Logunov D. V. 1991. Spiders of the superfamily Amaurobioidea (Aranei) from Sakhalin and Kurily Islands / / Ibid. Vol. 70. No. 9. P. 87 - 94 [in Russian, with English summary],", "Song DX, Zhu, M. S, Chen, J. 1999. The spiders of China. Hebei Science & Technology Press. 640 pp."]}